An Integrative Approach to Interconnective in Caknun Da'wah Among the Young Generation of Indonesia - Abdul Basit; Imam Alfi (Darul Yasin Al Sys, 2026)
Although conventional patterns of da‘wah continue to shape much religious communication, alternative approaches that more effectively engage the younger generation remain important to explore. This study aims to analyze the integrative-interconnective approach in Cak Nun’s da‘wah for the younger generation as an alternative to conventional patterns. This approach integrates intellectual, cultural, and spiritual dimensions through reflective, dialogical, and inclusive communication. The study employed a qualitative design using document analysis and participatory observation in the Maiyah forum. Data were analyzed thematically through interpretation, categorization, and critical reflection. The findings indicate the formation of a holistic da‘wah epistemology model that combines religion, art, science, and social reality. Theoretically, da‘wah is interpreted as the production of dialogical meaning across disciplinary boundaries. This study concludes that the integrative-interconnective approach offers a relevant alternative framework for engaging the younger generation through adaptive, inclusive, and reflective da‘wah practices. The findings contribute to the enrichment of the interconnected da‘wah paradigm and imply the need for the development of adaptive curricula and creative media-based da‘wah practices.